Variants of the gene encoding the beta subunit of pyrophosphate dependent phosphofructokinase (PFP) and their transcriptional expression in sugarcane - Reddy, Sanushka (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2001.